Religion, Social Practice, and Contested Hegemonies - Salvatore, Armando. author. aut Link
XIII, 249 p. 1 illus.
Keywords: This collection of essays examines how modern public spheres reflect and mask - often both simultaneously - discourses of order, contests for hegemony, and techniques of power in the Muslim world. It builds on scholarship that re-imagines theories and practices of the public in modern and contemporary societies. While examining disparate time periods and locations, each contributor views modern and contemporary public spheres as crucial to the functioning, and understanding, of political and societal power in Muslim majority countries.